Problem-Solving Exercises in Green and Sustainable Chemistry. - Matlack, Albert S. (Boca Raton : CRC Press LLC Florence : Taylor & Francis Group [distributor], 2017)
When confronted with a problem in science, the way to proceed is not always obvious. The problem may seem intractable or there may be many possible solutions, with some better than others. Problem-Solving Exercises in Green and Sustainable Chemistry teaches students how to analyze and solve real-world problems that occur in an environmental context, and it encourages creativity in developing solutions to situations based on events that have actually taken place. The problems described in this book are relevant and stimulating in learning and understanding the principles of green and sustainable chemistry. They address various aspects of the field, including: Toxicity Waste generation and disposal Chemical accidents Energy efficiency New policy development The final chapter contains proposed solutions to the presented problems and provides commentaries and references to relevant literature. This book also prompts students to become more comfortable with the idea of multiple "correct" answers to problems. It emphasizes the reality that green chemistry is about making practical decisions and weighing multiple factors that are often conflicting, thus making it difficult or impossible to apply one perfect solution to a given situation. Problem-Solving Exercises in Green and Sustainable Chemistry prepares students to solve challenging problems, whether as green chemists, as architects designing energy-efficient buildings, or as environmentally-conscious citizens.
OCLC-licensed vendor bibliographic record.
Keywords: Green chemistry -- Textbooks; Chemistry -- Textbooks; Environmental management -- Textbooks